The inductive effect of musical mode types on emotions and physiological responses: Chinese pentatonic scales versus Western major/minor modes - Jiang, Yihe; Zheng, Maoping (Frontiers in Psychology, 2024)
Background The value of music lies in its ability to evoke emotions. People can gain emotional experiences in music and can also regulate their own emotions through music. Music has its own structural rules, and exploring the relationship between musical structure and emotions is an important approach to understanding the mechanism of music-induced emotions. Musical mode refers to the arrangement of intervals around the tonic, presenting different musical modes based on the central tone and the arrangement of intervals, including Chinese pentatonic modes and Western major and minor modes. Musical morphology indicates significant differences in the construction intensity of traditional Chinese pentatonic modes and major and minor modes, affecting their mode forms and thus determining their adaptability to external influences. Aims Exploring the modalities of music and the effects of individual music training experiences on emotion induction; validating whether musical modes exhibit cross-cultural universality in the process of emotion induction. Method This study recruited 65 university students as participants (34 with music training experience, 31 without music training experience). Through a passive listening paradigm using the GEMS and combined with a biofeedback equipment, it explored the differences in behavioral and physiological indicators (skin conductance, temperature, heart rate) of emotional experiences (basic and aesthetic emotions) influenced by the modal forms of Chinese traditional pentatonic modes and Western major and minor modes. Results Firstly, the arousal level of music emotion is a primary factor influencing individuals’ aesthetic emotional experiences in music, which is related to the intensity of modal construction in music; Secondly, the emotional pleasure and skin temperature change induced by pentatonic music are greater than those induced by major and minor modes; Thirdly, the arousal level, electrodermal change, and heart rate variability of major and minor modes are greater than those of pentatonic music; Finally, music training experience enhances college students’ familiarity and preference for pentatonic music, thereby strengthening the electrodermal physiological indicators of emotional experiences. Conclusion The different modal forms of music express different levels of emotional arousal, leading to differences in individuals’ emotional dimensions and physiological indicators in music. Additionally, individuals’ music training experiences and cultural backgrounds also influence their experience of music emotions.